The Dangers and Risks of Smoking: A Social-Constructionist Analysis of Its Societal Impact - Rifka Cahaya Ulfa; Kailani Kusuma Ningrum (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
Smoking is not merely an individual health issue but a form of social complexity deeply interwoven with a society's values, customs, and everyday interactions. This study examines the dangers and risks of smoking with a specific focus on their community and social dimensions. It addresses a gap in the literature by analysing in depth how smoking behaviour is socially constructed, how it is socialised within families, peer groups, and communities, and how it subsequently affects collective quality of life. Adopting a qualitative, descriptive–exploratory design underpinned by the Theory of Social Construction, the research explores perceptions, experiences, and social meanings through in-depth interviews, focus group discussions, and participant observation, with the resulting data interpreted by means of reflexive thematic analysis. The findings indicate that smoking is routinely normalised and reproduced through observational learning and social pressure, generating substantial negative consequences that include inequitable second-hand exposure, economic strain on households, and disrupted patterns of social interaction. On this basis, the study argues for a decisive shift in tobacco-control strategy from individualistic interventions towards holistic, community-based approaches that deconstruct pro-smoking norms and empower communities to build environments that sustainably support health and a smoke-free way of life. The article's contribution is a systems-thinking model that renders these reinforcing and balancing dynamics explicit and locates the community as the principal point of leverage.